Dimensions of Legal, Justice and Gender Equality in Education - Abustan, Abustan; Siregar, Hamdan Azhar; Mustomi, Otom (AMCA, 2025)
Indonesia is a country based on the rule of law. As a country, with the fourth largest population in the world, the Indonesian state must always pay attention to all citizens in it, including women. The legal dimension provides firm guidance that all human beings, without distinction between women and men, because both are social beings, were created by the Almighty to develop a very important mission as